2021
DOI: 10.3390/biomedicines9081071
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion Weighted Imaging and T2 Mapping Detect Inflammatory Response in the Renal Tissue during Ischemia Induced Acute Kidney Injury in Different Mouse Strains and Predict Renal Outcome

Abstract: To characterize ischemia reperfusion injury (IRI)-induced acute kidney injury (AKI) in C57BL/6 (B6) and CD1-mice by longitudinal functional MRI-measurement of edema formation (T2-mapping) and inflammation (diffusion weighted imaging (DWI)). IRI was induced with unilateral right renal pedicle clamping for 35min. 7T-MRI was performed 1 and 14 days after surgery. DWI (7 b-values) and multiecho TSE sequences (7 TE) were acquired. Parameters were quantified in relation to the contralateral kidney on day 1 (d1). Ren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…Significant ADC reduction and T 2 prolongation suggest severe renal tissue damage at these time points. In previous studies, ADC reduction after AKI was reported to be associated with cell swelling and infiltration of inflammatory cells into the interstitial space [32,36,55]. Our results demonstrated ADC changes of OSOM only at day 6 after the intoxication of AAI.…”
Section: Discussionsupporting
confidence: 56%
“…Significant ADC reduction and T 2 prolongation suggest severe renal tissue damage at these time points. In previous studies, ADC reduction after AKI was reported to be associated with cell swelling and infiltration of inflammatory cells into the interstitial space [32,36,55]. Our results demonstrated ADC changes of OSOM only at day 6 after the intoxication of AAI.…”
Section: Discussionsupporting
confidence: 56%
“…Apparent diffusion coefficient (ADC) from DWI can be influenced by multiple factors including cellularity, the presence of macromolecules, and microcirculation. Previous preclinical studies revealed that ADC correlated with kidney volume loss and could be related to interstitial fibrosis induced by AKI, [22][23][24] although ADC showed lower sensitivity or lower correlation with kidney volume loss than transverse relaxation measures. 23,24 A more comprehensive and robust preclinical MLR model can be built by including additional MRI measures from CEST and DWI, obtaining temporal MRI and histological data after IRI, and increasing the sample size.…”
Section: Predicting Fibrosis and Ta Using Mlrmentioning
confidence: 87%
“…Previous preclinical studies revealed that ADC correlated with kidney volume loss and could be related to interstitial fibrosis induced by AKI, [22][23][24] although ADC showed lower sensitivity or lower correlation with kidney volume loss than transverse relaxation measures. 23,24 A more comprehensive and robust preclinical MLR model can be built by including additional MRI measures from CEST and DWI, obtaining temporal MRI and histological data after IRI, and increasing the sample size. Longitudinal MRI study of reversible as well as progressive IRI models, from acute phase to recovery or progression to CKD, will be very helpful to establish the method as an early diagnostic tool.…”
Section: Predicting Fibrosis and Ta Using Mlrmentioning
confidence: 87%
See 2 more Smart Citations